1999
DOI: 10.3406/psy.1999.28496
|View full text |Cite
|
Sign up to set email alerts
|

L'apprentissage de l'orthographe d'usage et ses troubles dans la dyslexie développementale de surface

Abstract: Summary : Learning to spell words : Difficulties in developmental surface dyslexia. Word spelling performance of normal children from the first to the fifth grade was analysed and compared with the performance of children having a reading and spelling impairment characteristic of surface dyslexia. The quantitative analysis of their productions for word spelling to dictation showed that the performance of children with surface dyslexia was very similar to that of younger control children of the same readin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 0 publications
2
9
1
4
Order By: Relevance
“…Thus, contrary to the delay hypothesis, the performance of dyslexic children may be qualitatively different from that of younger controls. This hypothesis was supported by Martinet and Valdois (1999) who showed that surface dyslexic children produced proportionally more phonologically plausible errors than reading-age matched children, even though their overall scores on exception word spelling did not differ; as a matter of fact, the proportion of phonologically accurate errors produced by these children was comparable to that of chronological age-matched controls (see however Curtin et al, 2001). Moreover, similarity of performance with younger control children tells us 'nothing about the causes of developmental dyslexia' (Bryant & Impey, 1986, p. 124) and does not rule out the possibility that developmental surface dyslexia derives from a specific underlying deficit.…”
Section: The Phonological Deficit Hypothesissupporting
confidence: 64%
“…Thus, contrary to the delay hypothesis, the performance of dyslexic children may be qualitatively different from that of younger controls. This hypothesis was supported by Martinet and Valdois (1999) who showed that surface dyslexic children produced proportionally more phonologically plausible errors than reading-age matched children, even though their overall scores on exception word spelling did not differ; as a matter of fact, the proportion of phonologically accurate errors produced by these children was comparable to that of chronological age-matched controls (see however Curtin et al, 2001). Moreover, similarity of performance with younger control children tells us 'nothing about the causes of developmental dyslexia' (Bryant & Impey, 1986, p. 124) and does not rule out the possibility that developmental surface dyslexia derives from a specific underlying deficit.…”
Section: The Phonological Deficit Hypothesissupporting
confidence: 64%
“…Danjon et Pacton, 2009;Martinet et Valdois, 1999;Rey, Pacton et Perruchet, 2005), nous avons opté pour une catégorisation des erreurs en fonction de leur plausibilité phonologique, c'est-à-dire selon leur capacité à altérer ou pas la forme phonologique du pseudomot. Les erreurs non phonologiquement plausibles (ENPP) apparaissent dans des productions telles que *carilu pour garilu alors que les erreurs phonologiquement plausibles (EPP) sont du type *nifurau pour nifuro.…”
Section: Variables Examinéesunclassified
“…Il a ainsi utilisé au hasard l'une des graphies connues du phonème [ã]. Il est intéressant de constater que la fréquence à laquelle les apprenants sont en contact avec un mot influence sa mémorisation, comme le précisent Cogis (2005), Jaffré (2003) ainsi que Martinet et Valdois (1999). L'élève 2aFO justifie d'ailleurs l'écriture du mot « lundi » en spécifiant : « C'est facile parce qu'on a un code de couleur à tous les jours, pis, il y a les jours de la semaine sur les calendriers ».…”
Section: Stratégies De Mémorisation Utilisées Lors De La Verbalisatiounclassified
“…Ces quatre stratégies semblent ainsi permettre aux élèves de mémoriser l'orthographe lexicale de plus de mots. Les trois premières stratégies, c'est-à-dire associer un graphème à un phonème, décomposer un mot en phonèmes et décomposer un mot en syllabes, sont associées aux phases phonologique et alphabétique de l'apprentissage puisque les élèves s'appuient sur les relations phonologiques pour écrire les mots (Bousquet et al, 1999;Fayol & Jaffré, 1999;Martinet & Valdois, 1999). La dernière stratégie, repérer les détails orthographiques, est associée aux phases morphographique et orthographique puisque les élèves utilisent les régularités de la langue (Bousquet et al, 1999;Fayol & Jaffré, 1999;Martinet & Valdois, 1999).…”
Section: Stratégies De Mémorisation Utilisées Lors De La Verbalisatiounclassified
See 1 more Smart Citation